Sexual Harassment and Bullying: A Guide to Keeping Kids Safe and Holding Schools Accountable - Strauss, Susan (Rowman & Littlefield Publishers, 2011)
Bullying in schools is often discussed, but sexual harassment in schools, and how it differs from bullying is often overlooked. In fact, though, sexual harassment (committed both by fellow students and school personnel) is more common and yet more easily and quickly dismissed by those involved, though its consequences for the victim can be profound. This book provides parents, teachers, school officials, and others with a framework comparing and contrasting sexual harassment and bullying as they relate to the behavior, laws, and impact on children. The author describes the responsibility of the school district and how parents and other adults can navigate the schools' policies, barriers, and responsibilities. She argues that children should not be subjected to bullying OR sexual harassment, that it is the school's responsibility to make the harassment or bullying stop, and that parents and other caring adults often need to be involved and advocate for the child, even against resistance from those in the school system. Throughout the book the author uses examples of actual cases that have made it to the courts and have been precedent setting and cases in which she has been involved as an expert witness or as a consultant. Resources for readers are also provided at the end of the book.